2010
DOI: 10.1007/s10151-010-0638-4
|View full text |Cite
|
Sign up to set email alerts
|

Salvage repair of anastomotic dehiscence following colon surgery using an expanded polytetrafluoroethylene graft

Abstract: Anastomotic dehiscence is a serious complication of colorectal surgery that causes death in up to 40% of cases in which it occurs. Edema and inflammation due to abdominal sepsis can prevent the use of standard management (i.e., colostomy, ileostomy or Hartmann's procedure), in which case alternative salvage repair methods are required. The present report describes the treatment of a 73-year-old female patient at high risk of mortality because of intraabdominal sepsis due to suture dehiscence following a right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The incidence of anastomotic dehiscence, a potential complication of colorectal surgery, is variable and may affect 1.8 to 12% of the cases 1 . It is associated with increased morbidity and mortality, hospital stay and total treatment costs 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of anastomotic dehiscence, a potential complication of colorectal surgery, is variable and may affect 1.8 to 12% of the cases 1 . It is associated with increased morbidity and mortality, hospital stay and total treatment costs 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, given the considerable complication rate, they do not qualify for being further assessed in this context. Implanted expanded polytetrafluoroethylene (ePTFE) graft (Uzun et al, 2010), or Dacron (Contieri et al, 1980) used to cover full thickness wall defects in the colon showed to function as a guide for ingrowing tissue that originated from the wound edges, thus, enabling closure of the respective tissue gap. They have nevertheless not been integrated into the regenerating tissue, but were eventually rejected.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…An either absorbable or non-absorbable polymer patch sutured into a full-thickness wall defect of stomach, small intestine, and even colon of different animal species generally showed to be initially integrated and overgrown by neomucosa, and eventually absorbed or intra-or extraluminally extruded (Thompson et al, 1986;Harmon et al, 1979;Contieri et al, 1980;Smyrnis, 1982). Though this approach has been revived in several publications reporting good results (Oh et al, 2002;Uzun et al, 2010), treatment of damaged bowel by implantation of synthetic material has never gained general acceptance in the surgical community, and is, therefore, out of common clinical practice. This may be due to the general concern regarding the use of synthetic material in tissue which is naturally colonized with bacteria, as it is particularly the case in the colon.…”
Section: Introductionmentioning
confidence: 99%